Sie sind auf Seite 1von 2

Proof of the Binomial Theorem 12.3.1

The Binomial Theorem says that: For all real numbers a and b and non-negative integers n,

For example,

(a + b) n =

n

r=0

n

r

a r b nr .

(a + b) 0 = 1,

+ b) 1 =

(a a + b,

+ b) 2 =

(a a 2 + 2ab + b 2 ,

(a + b) 3 = a 3 + 3a 2 b + 3ab 2 + b 3 .

Proof. Let P (n) be the statement that for all real numbers a and b, (a + b) n = n

r=0 n

r

a r b nr .

The Base Case is easy to establish. Now we prove the Inductive Step. Suppose that k Z is such that ‘inductive hypothesis’ (the formula for n = k, i.e., the statement P (k))

(a + b) k =

k

r=0

k

r

a r b kr .

(1)

We want to prove that ‘inductive conclusion’ (the formula for n = k + 1, i.e., the statement P (k + 1))

(a + b) k+1 =

k+1

r=0

k + 1

r

a r b k+1r .

We compute that

(a + b) k+1 = (a + b) k · (a + b)

k


=

r=0

=

k

r=0

k

r

k

r

a r b kr · (a + b) by the inductive hypothesis

a r+1 b kr +

k

r=0

k

r

a r b k+1r by the distributive property;

(2)

(3)

indeed, when we multiply a r b kr in line 2 by a, the power of a increases by 1 to get a r+1 b kr in the first term in line 3. Similarly, when we multiply a r b kr by a, we get a r b k+1r in the second term in line 3. Now a r b k+1r in line 3 of (3) matches the form of the right-hand side of (2). To make the term a r+1 b kr in line 3 of (3) also match, we shift the variable r down by 1 as follows. Define s = r + 1. Then r = s 1. Moreover, when r is summed from 0 to k, we then have that s is summed from 1 to k + 1. So the first term in line 3 of (3) may be rewritten as

k

r=0

k

r

a r+1 b kr =

k+1

s=1

1

s 1 a s b k+1s

k

(since k (s 1) = k + 1 s).

But s is just a name.

So we can replace s by r to get

Thus (3) implies that

k

r=0

k

r

(a + b) k+1 =

a r+1 b kr =

k+1

r=1

r

1 a r b k+1r .

k

k+1

r=1

r

1 a r b k+1r +

k

k

r=0

k

r

a r b k+1r .

We would like to combine the two sums on the right-hand side into one sum. But we have a slight mismatch in that the first sum is from 1 to k + 1 whereas the second sum is from 0 to k. So take out the r = k + 1 case from the first sum and we take out the r = 0 case from the first sum from the second sum and combine things in the following way:

(a + b) k+1 =

(k +

1) 1 a (k+1) b k+1(k+1) +

k

k

r=1

Since

(k+1)1 = k

k

k = 1 and k = 1, we have

0

r

1 a r b k+1r +

k

k

r=1

k

r

a r b k+1r + k

0

a 0 b k+10 .

(a + b) k+1 = a k+1 +

k

r=1

r 1 + k

r

k

a r b k+1r + b k+1 .

Since 1 r k, by Proposition 12.2.8 we have

r 1 + k

r

k

= k + 1

r

.

Hence

(a + b) k+1 = a k+1 +

k

r=1

k + 1

r

a r b k+1r + b k+1 .

But noting that a k+1 = k+1 k+1 a k+1 b 0 (is the r = k + 1 case in the sum) and b k+1 = k+1 a 0 b k+1 (is the r = 0 case in the sum), we see that

0

(a + b) k+1 =

k+1

r=0

k + 1

r

a r b k+1r .

This is the desired inductive conclusion (2). By mathematical induction, the proof of the Binomial Theorem is complete.

2